Innovative equity practices in government - Ramalho, Lívia; Mesquita Resende , Marília; Wehbe, Claudia; Silva de Lima , Marcelo Ivo (Revista del CLAD Reforma y Democracia, 2025)
The increasing diversity of the Brazilian population reflects the need for a public service that not only represents but also values the plurality of its employees. Although there have been advances in public policies and laws aimed at promoting inclusion, the reality is still marked by persistent inequalities. In this context, diversity and inclusion management plays an increasingly relevant role, being essential for creating a welcoming and equitable work environment. Innovative initiatives, such as those demonstrated here, promote inclusive practices and expand frameworks so that more organizations can multiply and transform their realities. In the Brazilian public administration, the Government Innovation Directorate (DINOV) and the innovative management lab LA-BORA! gov have made strides in promoting inclusive practices through diversity management and innovation, implementing methodologies such as OKR, women’s networks, and learning communities. These practices aim to create a more representative and equitable environment and serve as examples within the public service. These actions highlight the importance of cultivating work environments that value diversity, promote well-being, and ensure psychological safety, resulting in higher engagement, innovation and organizational sustainability.